Does Ownership Structure Matter For Publicly Listed Companies Performance In Malaysia? - Rozita Arshad (UUM Journal of Legal Studies, 2015)
The word of corporate governance has become a very important concept that requires many countries around the world to concentrate on its reformation. Globalisation of markets, open markets competition, and international business has generated awareness about the importance of improving corporate governance practices. Protecting shareholders and other stakeholders are also being attentive agenda and play important roles in corporate governance reforms due to ensure their value creation and their right as the owner of the shares. This article attempts to address this issue by examining the relationship between ownership structure and firm performance. The hypothesis is tested by assessing the impact of the structure of ownership on firm performance, using data for 237 Malaysia Public Listed Companies (PLCs). Therefore, this paper will provide an insight into further understanding on the issue of the relationship between ownership structure and firm performance